Analisis Perbedaan Produksi dan Pendapatan Usahatani Kakao Petani Anggota dan Non Anggota LEM (Lembaga Ekonomi Masyarakat) Sejahtera di Kecamatan Besulutu Kabupaten Konawe - Sari, Mila; Saediman, Haji; Limi, Muhammad Aswar (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2019)
This study aims to find out (1) the production and income of farmer cocoa farmers members and non-members of LEM Sejahtrera, (2) Differences in production and income of farmers' cocoa farming members and non-members of the Prosperous LEM. The population in this study were 273 cocoa farmers, using the proportionate stratified random sampling method obtained by 40 cocoa farmers from the Prosperous LEM group and 34 non-prosperous LEM cocoa farmers as the research sample. The results showed that (1) the average respondents production of Prosperous LEM members was 301 kg/ha/year and non-prosperous LEM members were 300 kg/ha /year, production of farmers and members of the Prosperous LEM were not significantly different from t_count = 0.105 greater than the significance of Î± = 0.05 (0.105> 0.05) with a confidence level of 95% (2) the average income of farmers in the Prosperous LEM members amounting to Rp3,607,384 and non-prosperous LEM farmers totaling Rp3,512,843, income for farmers and non-members of Prosperous LEM members was not significantly different from t_count = 0.367 greater than significance Î± = 0.05 (0.367> 0.05) with a confidence level of 95%